A Laboratory study of coronal microleakage using four temporary restorative materials - Cruz, E.V.
Aim: The aim of this study was to com pare the sealing abilities of Fermin and Canseal with the more popular temporary coronal filling materials. Cavit and Caviton.
Methodology: Standard access cavities were prepared in 160 intact human permanent molar teeth. They were divided into five groups consisting of 32 samples. The teeth were restored using one of the temporary filling materials, namely: Fermin, Canseal at two powder to liquid ratios, Caviton and Cavit. Thermal cycling and/or load cycling were applied on the samples. Assessment of microleakage utilized methylene blue dye penetration. Grading of the microleakage pattern was from 1 t 3, with 3 providing the best seal. Results were analyzed using two-way anova and by Fisher's PLSD post hoc test (P<0.05).
Result: Microleakage along Fermin, Caviton and Cavit samples did not go beyond Leakage Grade 2. Dye penetration into these materials was noted. This was not observed in the two groups of Canseal tested. However, the two groups of Canseal exhibited total leakage notably after being subjected to thermal cycling. There was a statistically significant difference in the microleakage scores obtained between the materials and conditions tested (P<0.0001).
Conclusion: Fermin was found to exhibit the best seal among the four materials tested followed by Caviton, and Cavit. Thermal cycling influenced the seal of certain load cycling.
Keywords: Dye penetration; Microleakage; Temporary filling materials